Kajian Toponimi Penamaan Desa di Kecamatan Cimanuk, Kabupaten Pandeglang, Provinsi Banten - Alifah, Alifah; Rosidin, Odin; Solihat, Ilmi (Universitas Lampung, 2025)
This journal explores the intersection of ethnolinguistics and toponymy, focusing on the naming conventions of villages in the Cimanuk District. The methodology employed in this research is ethnolinguistic with a descriptive qualitative approach. This method is particularly effective for understanding the nuances of language as it relates to cultural and social contexts. Intralingual matching is data analysis method focuses on analyzing the differences in linguistic elements, particularly phonological and lexical differences. The study categorizes the names based on grammatical units and their origins, revealing a total of 11 data points divided into monomorphemic (3 data) and polymorphemic (8 data) names. The analysis highlights that the naming process involves compounding, which is a significant aspect of word formation in language. The findings indicate that the names can be grouped into two aspects based on their origins: manifestation aspects (6 data) and societal aspects (5 data). This dual approach not only enriches the understanding of local culture but also emphasizes the importance of preserving cultural heritage through language.Keywords: Toponymy, Village Naming, Cimanuk, Grammatical Units